RE-EVALUATING LEARNING STYLE’S ROLE: PEDAGOGICAL AND ENVIRONMENTAL FACTORS OF ELEMENTARY IPAS ACHIEVEMENT - Hadiwangsa, Dyah Hayuningtrisna (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
This study is based on the assumption that teachers’ lack of awareness of students’ learning styles contributes to unsatisfactory learning outcomes. This quantitative descriptive study aims to find the relationship between students’ learning styles and their IPAS learning achievements. Data on the learning style of the research sample of 30 fifth-grade students at Mujahidin Elementary School in Pontianak was collected using a learning style questionnaire from Chislett and Chapman (2005). Meanwhile, learning achievement data was obtained from teacher documentation. The data analysis techniques used were normality test, homogeneity test, and One Way Anova test using SPSS software. The results showed that the students’ learning styles were dominated by visual learning styles at 60%, followed by auditory learning styles at 23,3%, and kinesthetic learning styles at 16,7%. The Anova test results showed a significance value of 0,134 (α > 0,05), indicating that there was no significant effect between the student’s learning style groups and their IPAS learning achievements. The finding of no significant effect confirms that there are other factors beyond learning style that are the source of problems in IPAS learning in elementary schools. The problem is multifactorial in nature, including internal and external aspects of students, along with the quality of innovative, varied, and relevant learning experiences provided by teachers. Therefore, the success of IPAS achievement transformation needs to prioritize strengthening students’ intrinsic motivation and enhancing teachers’ pedagogical competencies in designing differentiated and engaging learning activities, ensuring positive synergy across all internal and external elements.